Monitoring of lamotrigine concentrations in mothers, colostrum, and breastfed newborns during the early postpartum period - Kacirova, Ivana; Grundmann, Milan; Brozmanova, Hana (Biomedicine & pharmacotherapy, 2022)
OBJECTIVE: To analyse the concentrations of lamotrigine in maternal serum, colostrum, and serum of breastfed newborns, and to evaluate the effect of comedication with enzyme-inducing antiseizure medication and valproic acid. METHODS: This cohort study collected data from 158 women and 143 breastfed newborns. Maternal serum, milk (i.e., colostrum), and newborn serum samples were collected between the 2nd and 5th postnatal days, and lamotrigine concentrations were measured by high-performance liquid chromatography. RESULTS: The median lamotrigine concentrations were 2.7 mg/L in maternal serum, 1.4 mg/L in milk, and 1.7 mg/L in newborn serum. The median milk/maternal serum concentration ratio was 0.60, the median newborn/maternal serum concentration ratio was also 0.60, and the median newborn serum/milk concentration ratio was 1.00. A significant correlation was observed between milk and maternal serum concentrations and between newborn serum and milk concentrations, maternal serum concentrations, maternal daily dose, and dose related to maternal body weight. CONCLUSIONS: Exposure to lamotrigine in breastfed newborns is lower than exposure during pregnancy. However, by the same dose by the same mother, lamotrigine concentrations in both maternal serum and milk increase significantly after delivery. This finding, together with the immature function of eliminating enzymes in newborns, may be the reason for reaching concentrations in the reference range used for the general epileptic population in breastfed newborns. Therapeutic monitoring of breastfed newborns serum concentrations of lamotrigine is not mandatory; however, if signs of possible adverse events are noted, newborn serum concentrations should be analysed.
Keywords: Female; novorozenec; Lamotrigine; kolostrum; ženské pohlaví; Anticonvulsants; Postpartum Period; lamotrigin; mateřské mléko; lidé; Infant, Newborn; těhotenství; antikonvulziva; kohortové studie; Cohort Studies; Milk, Human; matky; Breast Feeding; Mothers; poporodní období; kojení; Pregnancy; Colostrum; Humans